GAMBARAN GEJALA HIPERSENSITIFITAS AKIBAT GELOMBANG ELEKTROMAGNETIK DARI BASE TRANSCEIVER STATION (BTS) DI KELURAHAN PADANG BULAN KECAMATAN MEDAN BARU TAHUN 2012 - Fatiyah Tul Khoir Nasution; Taufik Ashar; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2012)
Description Of Hypersensitivity Symptoms Result Of  Electromagnetic Wave From Base Transceiver Station (Bts) In Padang Bulan Medan Baru 2012. phone as communication equipment require electromagnetic wave to perform it’s function, making effect in the growing of Base Transceiver Station (BTS) which produces increasing of electromagnetic wave. Elektromagnetic wave gave effect the production of melantonin hormone which produced by the pineal gland. The result of it is hypersensitivity complaints, namely headache, disturbance of sleep, disturbance of concentration, constant fatigue, muscle pain and nausea. The purpose of this study was to determine the frequency of electromagnetic wave and symptoms of hypersensitivity of the Base Transceiver Station (BTS) in Padang Bulan Street Jamin Ginting Medan Baru District. The type of this research was descriptive cross sectional with 27 respondents were women who work as housewife, consist of 9 respondents whose house were used as BTS and 18 respondents who lived within 13 meters of the BTS. The result of distribution of questionnaires was given to 27 respondents, the highest hypersensitivity complaints were muscle pain, 25 respondents (92,6%), constant fatigue, 14 respondents (88,9%) and disturbance of sleep 17 respondents (62,9%). Government should control the emission of BTS’s electromagnetic wave and will not give permission to build of BTS at the top of society house.   Keywords : Base Transceiver Station (BTS), electromagnetic wave, hypersensitivity complaint